Exploring Gender Discourse in “Modern Women Bali” Media - Radha Andhra Swari (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study explores the construction of gender discourse in “Modern Women Bali” media. Drawing on gender theories and critical discourse analysis approach, this study aims to investigate how traditional gender roles and identities are articulated through media produced by women-based community of writers in Bali. Data were obtained from the Instagram posts of @modernwomenbali from January to July 2025, as well as five online magazine issues produced by Modern Women Bali. Utilizing qualitative method, this study analyzes the gender-related discourse that delve into how Balinese cultural values intersect with modern influences to shape gender narratives. The results revealed that Modern Women Bali actively embraces themes of women empowerment by correlating cultural expectations and modern reality. In conclusion, this study contributes to ongoing discussions in gender and media studies, especially in Bali.